Analisis Konsep Khilafah dalam Al Qur’an dan Sejarah - Suryani, Irma; Afrizal, Afrizal; Syawaluddin, Syawaluddin (UNIVERSITAS SERAMBI MEKKAH, 2025)
The reconstruction of the caliphate system has become a topic of debate among various Muslim communities, inspired by the past glory of Islam under this system. However, differing views on the concept of the caliphate have hindered reconstruction efforts. This study aims to explore the legal basis of the caliphate in the Qur'an and Islamic history using the maqâṣidi interpretation method and historical analysis. The findings reveal that the term